Anaphore et fonction attribut du sujet : le cas de SO - Elisabet Johansson-Manoury (Anglophonia)
This article deals with a particular kind of subject complement, and in so doing discusses the notions of “defining feature” and “subjective feature” in utterances where the adverb SO acts as an anaphora for the subject complement. The feature referred to by SO qualifies the subject, thus constituting a defining feature or a subjective qualification of the subject. The problem under scrutiny is the fact that I have stated elsewhere that the marker SO is linked to the notion of alterity: a feature of subjective origin involves the notion of alterity whereas a defining feature normally does not. In order to make these traits stand out the marker SO is opposed to one and Ø.